التخبيب وصوره المعاصرة في النكاح : دراسة فقهية تأصيلية - سلامي، علي محمد علي محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The family stability is one of the most important requirements of our life, so spoiling the relationship between the wife and her husband has many negative effects. Enticing a wife against her husband in order to spoil her relationhsip is not allowed in our religion. Therefore, the Shariah has addressed incitement by its texts, also the fuqaha '(may Allaah have mercy on them) were keen on adopting the jurisprudential provisions of this disgraceful act. The main purpose of this researsh is to concetrate at the findings of the jurists on this issue, and confirmation about the importance of having the stable life away from the problems that may lead to disperse. This is clear from the prohibition of inciting a woman against her husband in all its forms and holds accountable the one who causes it. The judge has the right to terminate of the marriage contract when he proved the spoiling, so this will deter anyone who begs himself to commit that spoil. However, the spoiler can marry the woman if her husband divorces her or dies. The spoiler deserves the punishment of reprimand by beating, imprisonment and fine, according to what the judge sees as a deterrent. All preventive and legal measures must be taken to reduce the spoiling, among these legal measures is the inclusion of a punishment for takhbib in a number of laws dealing with the preservation of the family entity, especially the Personal Status Act.